Does differential electricity pricing eliminate backward production facilities?——Evidence from China's manufacturing industry - Sun, Chuanwang; Xu, Zhehong; Tan, Bing; Zhan, Yanhong (Journal of cleaner production, 2024)
Backward production poses a critical global challenge, especially in developing countries. Differential Electricity Pricing (DEP) policy for energy-intensive industries aimed at countering backward productions since 2004 in China could be a promising and effective policy tool. This is a subject deserving of study, yet the policy effect is ambiguous. Hence, this paper delves into the impact of the DEP policy on backward production, specifically enterprise exiting, by utilizing differential estimations based on enterprise and urban data. Our findings consistently show that the DEP policy steadily increases the probability of energy-intensive enterprises opting to withdraw from the market, primarily driven by its effects on profits and investments. Notably, in the heterogeneity analysis, the DEP policy has more significant effects among non-state-owned, small-sized, and eastern enterprises. Furthermore, we establish a link between the DEP policy's effectiveness and local implementation, revealing that the stronger enforcement results in an enhanced DEP effect on backward production. In the further disscussion, it explores the DEP policy's repercussions on the industrial chain and cleaner production. In conclusion, valuable policy implications touching on industry, environment, overcapacity management, and enterprise exit strategies are provided.